Design and Validation of an Augmented Reality-Based Flipped Classroom Module to Enhance Trigonometric Conceptual Understanding - Dedi Pradesa; Efendi Napitupulu; Farihah Farihah (CV. Media Inti Teknologi, 2026)
Background: Mathematics learning, particularly trigonometry, is often considered difficult due to the abstract nature of the concepts and the limited use of interactive learning media. Conventional instruction tends to emphasize memorization rather than conceptual understanding, causing students to experience difficulties in visualization and mathematical reasoning.Aims: This study aimed to develop and validate an Augmented Reality-based flipped classroom module for trigonometry learning.Methods: This study employed a Design and Development Research (DDR) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The validation process involved material experts, media experts, and instructional design experts selected purposively based on their expertise. Data were collected using expert validation questionnaires with a five-point Likert scale and analyzed descriptively using percentage analysis.Results: The findings showed that the developed module achieved a “Very Good” category across all validation aspects. Material expert validation obtained percentages of 93%, 92%, and 97% for content feasibility, presentation feasibility, and language assessment, respectively. Media expert validation ranged from 94% to 98%, while instructional design validation obtained percentages of 96.00% and 92.73%. These results indicate that the module possesses high feasibility in terms of content quality, media usability, and instructional design. Conclusion: The developed module is feasible and appropriate for trigonometry learning and has the potential to support interactive and student-centered mathematics learning.